Evaluar potencial energético solar para la implementación de un sistema de generación alternativa mediante la energía fotovoltaica para la oxigenación en la crianza y reproducción de truchas en la finca san Nicolás en la provincia de Cotopaxi cantón Latacunga en el año 2016. - Gallardo Molina, Cristian Fabián (2016)
In this research the potential of solar energy for the purpose of electricity generation in the province of Cotopaxi Latacunga Canton parish Juan Montalvo Barrio Juan Pablo Segundo, Finca San Nicolás, located in the North part East of the city of Latacunga to 14 km to evaluate a height of 3280 meters of coordinates, based on the Solar Atlas of Ecuador issued by CONELEC, the Map of Global Solar Radiation, issued by the INAMHI, Database NASA Database UML and Station Meteorological of UTC-. Energy consumption in the Finca San Nicolás is evaluated by an analyzer of energy and power quality installed in the oxygenation system area fish farming for a period of one week, consumption is checked making an inventory of loads, especially oxygenators system. A literature review is made to establish an appropriate methodology to design a solar photovoltaic system connected to the (SFCR) network based on the useful area of generation. the technical and economic feasibility of incorporating a system of solar photovoltaic power generation SFCR type, the energy system of the Villa, in compliance with regulation 004/11 CONELEC, the Law on the Electricity Sector Regime and the Constitution is analyzed. Finally the design of a system of solar photovoltaic power generation as an alternative source of electrical energy which best suits facilities oxygenation system for the farm trout is proposed.